The role of the motor system in spinal pain: implications for rehabilitation of the athlete following lower back pain - Hodges, P. W. (Journal of Science and Medicine in Sport, 2000)
The purpose of this review is to consider the role of the motor system in spinal pain. It is well accepted that spinal stability is dependent on the contribution of the muscular system. However, the ability of this system to satisfy the requirements of stability is dependent on its controller--the central nervous system (CNS). The CNS must predict the outcome of movements to plan appropriate strategies of muscle activity to meet the demands of internal and external forces, and initiate appropriate responses to unexpected disturbances. In addition, this complex control of stability must occur in conjunction with control of the trunk muscles for other functions, such as respiration. For the CNS to cope with athletic performance the coordination of these parameters must be streamlined. Yet evidence suggests that when spinal pain is present the strategies used by the CNS to control trunk muscles may be altered. The mechanism for these changes is poorly understood but may be due to changes at many levels of the CNS. For rehabilitation of the athlete with spinal pain it is critical that the motor control of stability is optimised. Furthermore, this must be coordinated with the multiple other functions of trunk muscles, including respiration.